Comparative Studies of Gene Expression Kinetics: Methodologies and Insights on Development and Evolution - Gildor, Tsvia; Smadar, Ben-Tabou de-Leon (Frontiers in Genetics, 2018)
Across the animal kingdom, embryos of closely related species show high morphological similarity despite genetic and environmental distances. Deciphering the molecular mechanisms that underlie morphological conservation and those that support embryonic adaptation are keys to understand developmental robustness and evolution. Comparative studies of developmental gene regulatory networks can track the genetic changes that lead to evolutionary novelties. However, these studies are limited to a relatively small set of genes and demand extensive experimental efforts. An alternative approach enabled by next-generation sequencing, is to compare the expression kinetic of large sets of genes between different species. The advantages of these comparisons are that they can be done relatively easily, for any species and they provide information of all expressed genes. The challenge in these experiments is to compare the kinetic profiles of thousands of genes between species that develop in different rates. Here we review recent comparative studies that tackled the challenges of accurate staging and large-scale analyses using different computational approaches. These studies reveal how correct temporal scaling exposes the striking conservation of developmental gene expression between morphologically similar species. Different clustering approaches are used to address various comparative questions and identify the conservation and divergence of large gene sets. We discuss the unexpected contribution of housekeeping genes to the interspecies correlations and how this contribution distorts the hourglass pattern generated by developmental genes. Overall, we demonstrate how comparative studies of gene expression kinetics can provide novel insights into the developmental constraints and plasticity that shape animal body plans.